Understanding postharvest losses of pomegranate fruit in South Africa : magnitude, causes and impacts - Opara, Ikechukwu Kingsley (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPA)--Stellenbosch University, 2021.